AI's Potential Impact on Organization Venturing in Healthcare - Mishra, Anjay Kumar (GS WOW: Wisdom of Worthy Research Journal, 2025)
The editorial aims to enhance patent application practice among academician by illustrating content structure based on a published Indian patent with application no. 202441077427 dated on 11/10/2024 on name of . Dr. Santhi .V, Dr. Barkavi G. E, Dr. Devi. S, Mr. Arokiasamy. S, Mr. Ramesh. S, Dr. Sneha Master, Dr. Anjay Kumar Mishra, Dr. Suhas A Bhyratae, Mr. Srinivasan. V. S. S, Ms. Subhasheni A, Ms. R. Lavanya, Dr. K. Sumathi could be verified from https://iprsearch.ipindia.gov.in/PublicSearch/PublicationSearch/ApplicationStatus titled on Discussion on the AI's potential Impact on organization venturing in Healthcare in India. Artificial Intelligence (AI) is rapidly transforming the healthcare sector in India by enhancing organizational venturing through advanced data analytics and automation. AI technologies enable healthcare organizations to analyze vast patient data, improve diagnostic accuracy, optimize treatment plans, and predict disease trends, thereby improving patient outcomes and operational efficiency. Personalized medicine, driven by AI algorithms analyzing genetic and clinical data, offers tailored treatments that increase effectiveness and reduce side effects. However, challenges such as data privacy, ethical concerns, digital divide, high implementation costs, and the need for skilled professionals must be addressed. Overall, AI holds significant promise to revolutionize healthcare organizations in India, provided its adoption is managed ethically and inclusively.